Experimental heart failure causes depression-like behavior together with differential regulation of inflammatory and structural genes in the brain - Frey, Anna; Popp, Sandy; Post, Antonia; Langer, Simon; Lehmann, Marc; Hofmann, Ulrich; Sirén, Anna-Leena; Hommers, Leif; Schmitt, Angelika; Strekalova, Tatyana; Ertl, Georg; Lesch, Klaus-Peter; et al. (Frontiers in Behavioral Neuroscience, 2014)
Background-Depression and anxiety are common and independent outcome predictors in patients with chronic heart failure (CHF). However, it is unclear whether CHF causes depression. Thus, we investigated whether mice develop anxiety- and depression-like behavior after induction of ischemic CHF by myocardial infarction (MI). Methods and Results- In order to assess depression-like behavior, anhedonia was investigated by repeatedly testing sucrose preference for 8 weeks after coronary artery ligation or sham operation. Mice with large MI and increased left ventricular dimensions on echocardiography (termed CHF mice) showed reduced preference for sucrose, indicating depression-like behavior. 6 weeks after MI, mice were tested for exploratory activity, anxiety-like behavior and cognitive function using the elevated plus maze (EPM), light-dark box (LDB), open field (OF) and object recognition (OR) tests. In the EPM and OF, CHF mice exhibited diminished exploratory behavior and motivation despite similar movement capability. In the OR, CHF mice had reduced preference for novelty and impaired short-term memory. On histology, CHF mice had unaltered overall cerebral morphology. However, analysis of gene expression by RNA-sequencing in prefrontal cortical, hippocampal, and left ventricular tissue revealed changes in genes related to inflammation and cofactors of neuronal signal transduction in CHF mice, with Nr4a1 being dysregulated both in prefrontal cortex and myocardium after MI. Conclusions-After induction of ischemic CHF, mice exhibited anhedonic behavior, decreased exploratory activity and interest in novelty, and cognitive impairment. Thus, ischemic CHF leads to distinct behavioral changes in mice analogous to symptoms observed in humans with CHF and comorbid depression.